Strategi Ekspansi Perusahaan Global di Pasar Internasional : Analisis dan Tantangannya - Hendra Ibrahim; Irna Rianti (Jurnal Publikasi Manajemen Informatika, 2025)
The expansion of global companies into international markets is a crucial strategic step in enhancing growth and competitiveness. This study aims to analyze the strategies implemented by multinational companies in facing the dynamics of international markets as well as the challenges that arise during the expansion process. The research method used is qualitative analysis with case studies of several global companies, both successful and those encountering difficulties in international expansion. The main findings of this study indicate that the success of expansion depends not only on the right market penetration strategy but also on the company’s ability to adapt products, processes, and business models to local market conditions. Furthermore, the main challenges faced include cultural differences, strict regulations, and risky economic and political fluctuations. This study also identifies the importance of companies’ ability to build global networks, innovate, and effectively manage risks. Global companies face complex challenges in formulating expansion strategies in international markets. The results of this study contribute theoretically to the understanding of international expansion strategies and provide practical implications for companies planning to enter global markets.